Pendampingan Literasi Membaca Anak Migran Indonesia Melalui Metode Gamifikasi Puzzle di PKBM PNF KBRI Kuala Lumpur - Salza, Adelia Rifqa; Irfani, Muhammad Zidan; Suwari, Suwari; A’yun, Qurroti (Civiliza Publishing, 2025)
This reading literacy assistance program is carried out at the PKBM PNF KRI Embassy in Kuala Lumpur with the aim of improving the basic literacy skills of Indonesian migrant children through the application of the puzzle gamification method. This activity is motivated by low reading skills, vocabulary comprehension, and children's learning motivation which is limited by the lack of access to formal education. The mentoring was carried out for three weeks by applying an educational game-based service learning approach. The learning process is focused on five aspects, namely letter and sound recognition, syllable preparation, word reading, reading and intonation fluency, and learning attitude and motivation. The results of the activity showed a significant improvement in reading ability at the end of the program. In addition to cognitive improvement, participants also showed development in motivation, confidence, and teamwork skills. Thus, the puzzle gamification method has proven to be effective in improving the reading literacy of migrant children and can be used as an alternative learning strategy in non-formal education.